Analisis Persepsi Karyawan Pada Penerapan Undang-Undang Nomor 7 Tahun 2021 Tentang Harmoni Sasi Peraturan Perpajakan (Studi Persepsi Karyawan WNJ.ID tentang Penggunaan Nomor Induk Kependudukan (NIK) Sebagai Nomor Pokok Wajib Pajak (NPWP)) - Dayanti, Delita; Arafat, Fauzi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Tax, which is defined as a contribution to the state that can be enforced through law, has two functions, namely the budgetary function and the regular function. As a budgetary function, taxes act as a source of state revenue, which can then be used to finance state activities. Therefore, the size of the tax that can be collected has very important implications for the number and quality of activities that can be carried out by the state. The tax ratio in Indonesia is low because Indonesian citizens are less aware of registering with the Tax Service Office (KPP) and obtaining a Taxpayer Identification Number (NPWP), so that there are many economic activities that should be tax objects but are difficult or cannot be detected by the tax authorities. The growing shadow economy activities can cause state losses, because shadow economy actors are generally separated from the tax authorities, thus eliminating the obligation to pay taxes. The taxation system in Indonesia which is self-assessment in nature encourages taxpayers to have self-awareness to report and pay their tax obligations in their role and support state revenues in order to achieve the common welfare of the people. To report and pay tax obligations, taxpayers must have a Taxpayer Identification Number (NPWP) as tax identity. Taxpayer Identification Number (NPWP) is a number given to taxpayers as a means in tax administration which is used as personal identification or Taxpayer identity in carrying out their tax rights and obligations, Taxpayer Identification Number (NPWP) is a means in tax administration which used as personal identification or taxpayer identity, each taxpayer is only given one taxpayer identification number. Taxpayer identification numbers are also used to maintain order in tax payments and in supervising tax administration, so that taxpayers' Taxpayer Identification Numbers (NPWP) obtain several other direct benefits, such as paying taxes in advance (installments\tax credits) on external taxes. paid when the taxpayer goes abroad, as a requirement when processing a trading business permit (SIUP), and as one of the conditions for creating a checking account at banks, taxpayers who do not register to obtain a taxpayer identification number are subject to witnesses in accordance with the provisions of tax laws and regulations. The survey results show that respondents have a positive perception regarding the benefits of the policy of integrating Population Identification Numbers (NIK) into Taxpayer Identification Numbers (NPWP) in increasing efficiency and ease in processing tax documents, verifying identity, the number of documents that need to be prepared, and access to services. online tax.